2016
DOI: 10.1016/j.cmet.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the CNS and Periphery Coordinate Lipophagy and Lipolysis in the Brown Adipose Tissue and Liver

Abstract: Summary Autophagy degrades lipid droplets (LD) via lipophagy. Cytosolic lipases, ATGL and HSL, are canonical mechanisms for lipolysis. Whether autophagy proteins engage in direct crosstalk with lipases to promote lipid mobilization remains unknown. The integrative physiology of an inter-organ communication in lipophagy regulation is also unknown. Here, we show that cold induces autophagy in proopiomelanocortin (POMC) neurons, and activates lipophagy in brown fat (BAT) and liver in mice. Targeted activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
232
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(245 citation statements)
references
References 34 publications
8
232
4
1
Order By: Relevance
“…41 The apparent contradiction of this observation with our current findings will deserve further research. However, the complex intracellular machinery associated with thermogenic activation in brown adipocytes (including UCP1 protein increase) is known to be minimally developed in such a very short-time cold exposure setting and, in fact, shivering is the major response to very short-time acute exposure to cold.…”
Section: Discussioncontrasting
confidence: 60%
“…41 The apparent contradiction of this observation with our current findings will deserve further research. However, the complex intracellular machinery associated with thermogenic activation in brown adipocytes (including UCP1 protein increase) is known to be minimally developed in such a very short-time cold exposure setting and, in fact, shivering is the major response to very short-time acute exposure to cold.…”
Section: Discussioncontrasting
confidence: 60%
“…Induction of lipophagy is part of a complex cellular and physiological response to several stimuli such as starvation [5], β-adrenergic stimulation [29], fatty acid loading [5], and cold exposure [30 ▪▪ ]. Accordingly, negative (Fig.…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…Though mTOR inhibition is not a very specific way to enhance lipophagy, it has been shown to do so in-vivo in several contexts. Martinez-Lopez et al [30 ▪▪ ] showed induction of lipophagy specifically in the brain with rapamycin reduced lipid accumulation in an autophagy-dependent fashion. Remarkably, using rapamycin to drive lipophagy or ATG7 silencing to block lipophagy was sufficient to drive efferent neural signaling to induce matching lipophagic responses in brown adipose tissue and liver.…”
Section: Regulation Of Lipophagymentioning
confidence: 99%
“…Elevated T3 in ARC appeared to accelerate UCP2-dependent mitochondrial uncoupling in neuropeptide Y/AgRP neurons, leading to consequent rebound feeding following food deprivation [74]. The observation that TH regulates POMC expression in the ARC may be relevant for cold-induced BAT thermogenesis as a recent study showed that cold exposure induces autophagy in hypothalamic POMC neurons, which is necessary to activate lipophagy in BAT and the liver through the sympathetic network favoring cold-induced thermogenesis [75]. …”
Section: Systemic Effects Of Intrahypothalamic Thmentioning
confidence: 99%